Linear thermal expansion behavior of compacted bentonite buffer materials - Seok Yoon; Gi-Jun Lee; Gyu-Hyun Go (Case Studies in Thermal Engineering, 2022)
In a geological repository system, buffer is indispensable to ensure the safe disposal of high-level radioactive waste (HLW). Because heat generated from spent nuclear fuel in a canister is released to the surrounding buffers, thermal properties of such materials are fundamental in determining the overall disposal safety. Specifically, given that thermal expansion causes thermal stress to canisters and intact rock masses in the near-field location, it is imperative to evaluate the thermal expansion characteristics of the buffer, particularly when bentonite is used. This study investigates the linear thermal expansion properties of Kyeongju bentonite buffer, a type of Ca-bentonite produced in South Korea. The linear thermal expansion coefficient of dried bentonite was measured considering the heating rate, dry density, and temperature variation using dilatometer equipment. The linear thermal expansion coefficient values of the KJ bentonite buffers were found to be 4.0–6.2 × 10⁻⁶/°C. Based on test results, a numerical analysis was conducted, and the thermal strain values were similar between the test and numerical analysis. The overall linear thermal expansion coefficient of the KJ bentonite, considering radially confined or unconfined conditions and dried or saturated states, was predicted to be between 3.2 × 10⁻6/°C and 1.0 × 10⁻5/°C.